Avaliação nutricional de fenos de resíduos da bananicultura submetidos a diferentes métodos de secagem - Sarah Silva Santos (2020)
The objective of this work was to evaluate the effect of including waste banana crop submitted to different drying processes on consumption, apparent digestibility of nutrients and respirometric parameters in diets of growing lambs. Twenty lambs were used, with an average body weight of 20 kg, housed in metabolic cages in a randomized block design, with five treatments: Hay Cynodon spp. as a control treatment, hay from banana leaves dried in the shade or in the sun, and hay from banana leaf dried in the shade or in the sun. The consumption and apparent digestibility of nutrients in metabolic cages were evaluated and the animals were subsequently transferred to a respirometric chamber where the assessment of oxygen consumption and production of carbon dioxide and methane (CH4) of the animals in maintenance or ad libitum fed in open circuit respirometry system was mesuared. The data were analyzed in analysis of variance and the means compared by the Scott-Knott test at the level of 5% probability. The consumption of dry matter, organic matter, crude protein and neutral detergent fiber were not influenced by the treatments (P>0.05). The pseudostem hays in both drying methods showed higher digestibility coefficients of dry matter (76.00%), organic matter (76.75%) and neutral detergent fiber (59.75%), possibly due to the presence of tannins in leaves, the apparent digestibility of crude protein was not influenced by the type of hay or drying method (P>0.05). The consumption of digestible, metabolizable and liquid energy was not influenced by the type of hay or drying method. The different hays and drying methods did not influence the respirometric parameters, gas exchange and heat production of animals ad libitum fed (P>0.05). For the animals maintenance fed, there was variation in CH4 production and respiratory coefficient (CR). The loss of energy in the form of methane was lower for animals fed with leaf hay (P<0.05), possibly the tannin present in the leaves reduced the production of ruminal methane. The same behavior was observed for CR, with the lowest values observed for leaf hays (P<0.05), possibly reflecting the lower content of non-fibrous carbohydrates in the diets based on these by-product.